Targeted Expression of Myelin Autoantigen in the Periphery Induces Antigen-Specific T and B Cell Tolerance and Ameliorates Autoimmune Disease - Na, Shin-Young; Krishnamoorthy, Gurumoorthy (Frontiers in Immunology, 2021)
There is a great interest in developing antigen-specific therapeutic approaches for the treatment of autoimmune diseases without compromising normal immune function. The key challenges are to control all antigen-specific lymphocyte populations that contribute to pathogenic inflammatory processes and to provide long-term protection from disease relapses. Here, we show that myelin oligodendrocyte glycoprotein (MOG)-specific tolerance can be established by ectopic expression of MOG in the immune organs. Using transgenic mice expressing MOG-specific CD4, CD8, and B cell receptors, we show that MOG expression in the bone marrow cells results in impaired development of MOG-specific lymphocytes. Ectopic MOG expression has also resulted in long-lasting protection from MOG-induced autoimmunity. This finding raises hope that transplantation of autoantigen-expressing bone marrow cells as a therapeutic strategy for specific autoantigen-driven autoimmune diseases.